“Feito à mão e com amor”: alinhavos etnográficos acerca de saberes e fazeres de costureiras na cidade de Santa Maria/RS - Käercher, Karen Ambrozi (2018)
The present study discourse about the universe of women's knowledge and practices, of threads and needles, cloths and sewing machines that were empirically and, somehow, continue to be passed on from generation to generation. Among the knowledges and doings that surround the feminine world, it is in the know-how of sewing that resides the focus of this dissertation that has as protagonists the home workers. To that end, my research locus is concentrated mostly in the city of Santa Maria/ RS, although I have also interacted with two interlocutors who live in other cities and who played a relevant role in the development of the research. From the memories of nine women seamstresses about their trajectories in the work world, I’ve try to understand how the practice of sewing endures while knowing how to do in their daily lives, taking into account the technological, demographic changes and the world of work itself. Through work narratives, interviews, participant observation, sketches, excerpts from literary works and memories allied to photographs, I try to "sew", in this dissertation, the ethnographic method of duration and street ethnography. Thus, fieldwork was carried out in the street environment, in the dressing rooms and in the domestic environment, that is, in the sewing rooms. By situating the seam as an ever-changing element of life, I sought to show that sewing persists over time even in the face of changes in the way we dress and produce clothing in our society. I have observed that sewing remains as a predominantly feminine work and continues to be performed in the home considering the possibility of reconciling it with the work of caring for people and the home environment. The sewing is also preserved as a know-how transmitted between women of different generations. In addition, the context of Santa Maria that presents itself as a university and military city, favors the permanence of sewing practices in view of the demand for services by this public, such as the making of party dresses and military uniforms. These circumstances reveal how sewing reverberates in practices, in the city, in the bodies, and in the lives of seamstress women.